(untitled) (International Journal of Nursing Education, 2021)
Diabetes educator (DE) has a clear and important role in the overall management of patients with diabetes in all stages of care by providing much needed detailed information and support on adequate understanding of the pathology and safe-execution of the prescription by the specialist and other life-style changes to combat diabetes effectively. This is more significant in countries like India where there is an unfavourable ratio of physicians to patients with diabetes. The accessibility of the health-care team by the huge number of patients with diabetes in the government hospitals and consequent rush hours can be effectively compensated by the DE by relieving the physician of routine and repeated individual counselling contributing to effective physician utilization and avoiding fatigue and burnout. Literature has evidence that this cost-effective intervention can improve patient outcome and warrants more investment in formal training and continuous academic development of DEs. In this manuscript, a step-by-step counselling of patients with diabetes is described for easy understanding and execution.